Big Book as an Effort to Increase Beginning Reading in SD Negeri Percobaan, Medan City - Laily Sa’idah; Isda Pramuniati; Evi Eviyanti (BIRCU, 2020)
This research elaborates the material development of beginning reading for students Grade II SD Negeri Percobaan Medan through Big Book Media. The method of the research is Research and Development ( R & D) which consists of 10 steps of research, namely (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) product testing , (7) product revisions, (8) usage trials, (9) product revisions and, (10) mass production. This research was conducted at SD Negeri Percobaan Medan Medan Baru District held in the odd semester of the 2017/2018 academic year. The research was carried out on Indonesian language learning by using Big Book media. The results obtained in this study show that the teaching materials are appropriate and valid for using by Grade II primary school students because they have been assessed and validated from the expert team. This conclusion was taken based on the results of the analysis of experts consisting of grammar experts in fairly decent qualifications (82%), material content experts were in very decent qualifications (94%) and learning design experts were in decent qualifications (73%). From all validator assessments, there were sufficient qualifications with an average value of 83%. This is reinforced by the results at the product trial stage obtained a percentage of 53.33% and the trial phase of use obtained a percentage of 86.66%. This means that indicators of effectiveness have been fulfilled. So with the results obtained it can be stated that the development material is appropriate to be used in Grade II SD Negeri Percobaan in order to improve reading skills in the implementation of a better learning process.